Reliability and safety of long-term dabigatran use in patients with atrial fibrillation - E. V. Serdechnaya; S. V. Yurieva; B. A. Tatarskyi (Российский кардиологический журнал, 2013)
The paper presents the data on effectiveness and safety of long-term dabigatranuse for the prevention of thromboembolic complications in patients with atrialfibrillation (AF). The criteria for selecting an optimal dose of dabigatran arediscussed. The authors summarise the results of the current international andRussian clinical guidelines on dabigatran use in AF patients.